Synergistic antitumor effects of astragalus polysaccharide: a preclinical systematic review and meta-analysis - Zhang, Ruo; Yang, Qian; Chen, Zhi; Huang, Jianming; Zhang, Guonan (Frontiers in Pharmacology, 2025)
BackgroundAccumulating evidence suggests that astragalus polysaccharide (APS) may enhance the efficacy of conventional cancer therapies through multiple mechanisms. However, the synergistic effects of APS have not been systematically quantified. This meta-analysis was therefore conducted to quantify these potential synergistic antitumor effects and provide preclinical evidence to inform future clinical trials.MethodsFollowing PRISMA 2020 guidelines, we systematically searched ten databases (including PubMed and Web of Science) for preclinical studies from inception to May 2025 using predefined inclusion criteria. Risk of bias was assessed using SYRCLE’s RoB tool. Meta-analyses and subgroup analyses were performed using RevMan 5.4.1, while publication bias was assessed via funnel plots and Egger’s test (Stata 17.0). This systematic review was prospectively registered in PROSPERO (registration number: CRD420251047751).ResultsForty-one publications (44 independent studies) involving 748 animals were included. APS combination therapy was associated with significant improvements in tumor-related outcomes, including reduced tumor weight and volume, suppressed metastasis, and prolonged survival. Mechanistically, APS co-administration enhanced CD8+ T-cell infiltration, increased splenic and thymic indices, modulated cytokine profiles (TNF-α, IL-2, IFN-γ, IL-12, IL-6, IL-10), and reduced PD-1/PD-L1 expression in tumor tissue. Additionally, APS appeared to alleviate chemotherapy-induced nephrotoxicity, as evidenced by lower serum creatinine levels. Subgroup analyses indicated that heterogeneity was partially explained by model type, APS dosing regimen, and combination therapy modality. The certainty of evidence for primary outcomes was rated as low or very low according to the GRADE assessment.ConclusionThis meta-analysis provides preclinical evidence that APS may serve as an adjunctive agent to enhance the efficacy of conventional cancer therapies. However, given the low certainty of current evidence, further mechanistic studies and well-designed clinical trials are urgently warranted to establish its efficacy and therapeutic role in oncology.Systematic Review RegistrationPROSPERO 2025 CRD420251047751 https://www.crd.york.ac.uk/PROSPERO/view/CRD420251047751